Pro ASP.NET 2.0 in C# 2005 - MacDonald, Matthew (Apress, 2012)
In this book, you’ll learn everything you need to master ASP.NET 2.0. If you’ve programmed with a previous version of ASP.NET, you’ll sail through the basics and quickly begin learning about the exciting new features in version 2.0. If you’ve never programmed with ASP.NET, you’ll find that this book provides a well-paced tour that leads through all the fundamentals, along with a backstage pass that lets you see how the ASP.NET internals really work. The only requirement for this book is that you have a solid understanding of the C# language and the basics of .NET. If you’re a seasoned Java or C++ developer but you’re new to C#, you may find it easier to start with a book about .NET fundamentals before you read this one. Try C# and the .NET 2.0 Platform, Third Edition (Apress, 2005) for a comprehensive introduction or, for a quicker start, read A Programmer’s Introduction to C# 2.0, Third Edition (Apress, 2005).